OP0058 Improvement in patient-reported outcomes in patients with polyarticular-course juvenile idiopathic arthritis and inadequate response to biologic or non-biologic disease-modifying antirheumatic drugs treated with sc abatacept. (15th June 2017) - Ruperto, N; Brunner, H; Tzaribachev, N; Vega-Cornejo, G; Louw, I; Anton, J; Viola, D; Foeldvari, I; Keltsev, V; Kingsbury, D; Wouters, C; Lauwerys, B; et al.
Abstract : Background: In patients (pts) with polyarticular-course juvenile idiopathic arthritis (pJIA), SC abatacept (ABA) 125 mg weekly has a similar pharmacokinetic profile, therapeutically equivalent efficacy and comparable safety to IV ABA 10 mg/kg every 4 weeks. 1 Although some data on paediatric pt-reported outcomes (PRO) have been published for IV ABA, 2 PRO data following treatment with SC ABA have not. Objectives: This analysis examined the effect of SC ABA treatment on PROs (activities of daily living [ADL] limitation questionnaire of parent/caregiver, childhood HAQ [CHAQ]-DI, and parent global assessment of overall pt well-being [PaGA]) in 6–17-year pts with active pJIA in a Phase III trial (NCT01844518 ). Methods: Pts with pJIA aged 2–17 years with an inadequate response/intolerance to ≥1 DMARD were enrolled in this single-arm, open-label study and received SC ABA weekly for 4 months based on body weight tier (10–<25 kg [50 mg ABA], 25–50 kg [87.5 mg ABA] and >50 kg [125 mg ABA]). JIA-ACR 30 criteria (ACR Pediatric 30) responders at Month 4 could receive ABA for another 20 months. For the 6–17-year cohort reported here, ADL limitation questionnaire of parent/caregiver (mean [SD] number of days [D] of parental/caregiver missed activity, paid care and missed school [absolute values per month and percentage of D missed per month relative to an assumed average of 20 school D/month]); CHAQ-DI (0–3 scale across 8 domains of disability component); and PaGA (0–100 mm visual analogue scale) were evaluated. Results: Baseline characteristics of the 173 pts with pJIA from the 6–17-year cohort were: median (min, max) age, 13.0 (6.0, 17.0) years; median (min, max) number of active joints, 10.0 (2.0, 42.0); 78.6% of pts used MTX (median dose: 11.6 mg/m 2 /week); and 26.6% were with prior biologic failure. All ADL limitation components improved from baseline to D113 (Month 4); these improvements were largely maintained at D309 (Figure). Relative percentage D missed from school decreased from 15% (D1) to 5.5% (D309, Figure D). CHAQ-DI and PaGA improved from baseline to D309 (Table). Further 2-year data are pending. Conclusions: In this analysis of patients with pJIA aged 6–17 years, SC abatacept demonstrated a beneficial effect on PROs including reductions in activity limitation and disability (CHAQ-DI) and improvement in well-being (PaGA) up to D309. References: Lovell D, et al. Arthritis Rheumatol 2016;68(suppl 10): Abstract 948. Ruperto N, et al. Arthritis Care Res 2010;62:1542–51. Disclosure of Interest: N. Ruperto Grant/research support from: The G. Gaslini Hospital has received contributions from the following industries for the coordination activity of the PRINTO network: Bristol-Myers Squibb, GlaxoSmithKline, Hoffman-La Roche, Novartis, Pfizer, sanofi-aventis, Schwarz Biosciences, Abbott, Francesco Angelini S.P.A., Sobi, Merck Serono, Consultant for: AbbVie, Amgen, Biogen Idec, Alter, AstraZeneca, Baxalta Biosimilars, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Crescendo Bioscience, EMD Serono, Hoffman-La Roche, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo Nordisk, Pfizer, sanofi-aventis, Servier, Takeda, UCB Biosciences GmbH, Speakers bureau: AbbVie, Amgen, Biogen Idec, Alter, AstraZeneca, Baxalta Biosimilars, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Crescendo Bioscience, EMD Serono, Hoffman-La Roche, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo Nordisk, Pfizer, sanofi-aventis, Servier, Takeda, UCB Biosciences GmbH, H. Brunner: None declared, N. Tzaribachev: None declared, G. Vega-Cornejo: None declared, I. Louw: None declared, J. Anton Grant/research support from: Bristol-Myers Squibb, Novartis, Pfizer, AbbVie, GSK, Sobi, Roche, Alexion, Sanofi, Genzyme, Consultant for: Novartis, Sobi, Roche, Gebro, Pfizer, AbbVie, Alexion, Speakers bureau: Novartis, AbbVie, Pfizer, Sobi, Roche, Gebro, D. Viola: None declared, I. Foeldvari: None declared, V. Keltsev: None declared, D. Kingsbury: None declared, C. Wouters: None declared, B. Lauwerys: None declared, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, R. Wong Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Nys Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Banerjee Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, A. Martini: None declared, D. Lovell Grant/research support from: National Institutes of Health, NIAMS, Consultant for: AstraZeneca, Bristol-Myers Squibb, AbbVie, Pfizer, Roche, Novartis, UBC, Forest Research Institute, Horizon, Johnson & Johnson, Biogen, Takeda, Genentech, GlaxoSmithKline, Boehringer Ingelheim, Celgene, Janssen, Speakers bureau: Genentech